2020
DOI: 10.1002/hep4.1523
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib Versus Nivolumab After Sorafenib Failure: Real‐World Data in Patients With Hepatocellular Carcinoma

Abstract: Regorafenib and nivolumab are drugs approved for second-line treatment of patients with hepatocellular carcinoma (HCC) after sorafenib failure. However, the effectiveness of regorafenib and nivolumab following sorafenib has not been directly compared. This study retrospectively evaluated 373 patients with HCC who were treated with regorafenib (n = 223) or nivolumab (n = 150) after sorafenib failure between July 2017 and February 2019. Progression-free survival (PFS; hazard ratio [HR], 0.85; 95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…analyses [18]. Consequently, these real-world clinical experiences indicated that using nivolumab might produce consistent OS compared to using regorafenib for patients after sorafenib failure.…”
Section: Discussionmentioning
confidence: 98%
“…analyses [18]. Consequently, these real-world clinical experiences indicated that using nivolumab might produce consistent OS compared to using regorafenib for patients after sorafenib failure.…”
Section: Discussionmentioning
confidence: 98%
“…The reason why cemiplimab, atezolizumab, avelumab, durvalumab have not been included in the guidelines for the treatment of HCC is that their efficacy and safety is not completely certain, and several trials are still ongoing (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Nivolumab as a first-line treatment option compared with sorafenib is still under research, and nivolumab may become first-line treatment if the result is positive (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23); atezo+bev has potential as a first-line treatment for unresectable HCC; both avelumab and axitinib are known to be safe when administered as monotherapy; cemiplimab and durvalumab have also demonstrated effectiveness in ORR (30,33,35,37,40). With an increase in the number of clinical trails, cemiplimab, atezolizumab, avelumab and durvalumab may be added to the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Nivolumab plus ipilimumab was evaluated in patients with advanced HCC pretreated with sorafenib. The ORR was 31%, disease control rate (DCR) was 49% and a median duration of response was 17 months ( 22 ). NCCN recommends nivolumab as a subsequent therapy following disease progression in patients with CPA (Child-Pugh class A) or CPB (Child-Pugh class B) disease (a category 2A recommendation) ( 23 ).…”
Section: Listed Drugsmentioning
confidence: 99%
“… 25 Another real-world study compared the effectiveness of regorafenib (n=223) and nivolumab (n=150) after sorafenib failure and demonstrated that only one patient (0.7%) in the nivolumab group but none in the regorafenib group achieved a CR. 26 Joerger et al 27 presented the case of a sorafenib-refractory patient probably experiencing progressive disease during ICI combination treatment with the anti-PD-1 monoclonal antibody nivolumab and the anti-Glucocorticoid Induced Tumor Necrosis Factor Receptor (anti-GITR) monoclonal antibody BMS-986156 within a clinical phase-1 trial followed by a prolonged tumor response according to RECIST v 1.1 during third-line treatment with regorafenib. In this case, sorafenib-immunotherapy-regorafenib sequential treatment was applied and the last evaluation was documented as PR and the patient started taking regorafenib at a reduced dose of 80mg and later further reduced to 40mg per day.…”
Section: Discussionmentioning
confidence: 99%